2013
DOI: 10.1186/1756-0500-6-403
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide analysis of simple sequence repeats in maize and the development of polymorphism markers from next-generation sequence data

Abstract: BackgroundMaize (Zea mays ssp. mays L.), as the most important plant for staple food of several million people, animal feed and bioenergy productions, is widely cultivated around the world. Simple sequence repeats (SSRs) are widely used as molecular markers in maize genetics and breeding, but only two thousands pairs of SSRs have been published currently, which hardly satisfies for the increasing needs of geneticists and breeders. Furthermore, the increasing studies have revealed that SSRs also play a vital ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 43 publications
(45 reference statements)
5
24
0
4
Order By: Relevance
“…A/T motifs were also found to be the most abundant mononucleotide motifs in castor beans, rubber, Cocos nucifera and rice, while C/G motifs were found to be most abundant in sorghum, maize and Ganoderma lucidum. AT/TA motifs were also found to be the most abundant dinucleotide motifs in sorghum and maize, and AG/CT motifs were found to be the most abundant in castor beans, barley, rubber, Cocos nucifera, rice, coffee and mushrooms (Kantety et al 2002, Poncet et al 2006, Zhang et al 2007, Feng et al 2009, Yonemaru et al 2009, Qiu et al 2010, Qian et al 2013, Qu and Liu 2013, Xia et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…A/T motifs were also found to be the most abundant mononucleotide motifs in castor beans, rubber, Cocos nucifera and rice, while C/G motifs were found to be most abundant in sorghum, maize and Ganoderma lucidum. AT/TA motifs were also found to be the most abundant dinucleotide motifs in sorghum and maize, and AG/CT motifs were found to be the most abundant in castor beans, barley, rubber, Cocos nucifera, rice, coffee and mushrooms (Kantety et al 2002, Poncet et al 2006, Zhang et al 2007, Feng et al 2009, Yonemaru et al 2009, Qiu et al 2010, Qian et al 2013, Qu and Liu 2013, Xia et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Так, анализ результатов секвенирования отдельных хромосом или всего генома ряда злаковых и кукурузы (Zhang et al, 2007;Qu, Liu, 2013;Sergeeva et al, 2014) указывает на то, что наибoлее часто встречаются динуклеотидные повторы, затем частота встречаемости убывает при уве-личении длины повторяющегося мотива. Полученные нами результаты по анализу микросателитных локусов, по данным секвенирования выборки из 130 ВАС-клонов, также указывают на более высокую распространенность динуклеотидных последовательностей (253 последова-тельности), по сравнению с три-(156) и тетра-нуклеотид-ными (27) повторяющимися последовательностями ДНК.…”
Section: особенности организации микросателлитных локусов хромосомы 5вunclassified
“…Встречаемость ди-, три-и тетра-пов-торов варьирует также и в зависимости от участка генома. Оценка распределения ди-и тринуклеотидных повторов в транслируемых и нетранслируемых районах генных локусов показала, что встречающиеся в кодирующих районах генов микросателлиты более чем на 87 % состоят из тринуклеотидов, причем это характерно, например, как для риса, так и для кукурузы (Zhang et al, 2007;Qu, Liu, 2013). Это связано с тем, что увеличение копийности в тринуклеотидном повторе не приводит к сдвигу рамки считывания, и в ряде случаев может поддерживаться естественным отбором.…”
Section: особенности организации микросателлитных локусов хромосомы 5вunclassified
See 1 more Smart Citation
“… Settles et al (2014) have conveniently catalogued these indels (see their Table S1) and shown that 22–31% of these indels are also polymorphic with B73 × W22 and Mo17 × W22 populations, respectively. Resequencing of diverse maize inbred lines has produced more than 100,000 potentially polymorphic SSR loci that have been catalogued ( Qu and Liu, 2013 ; Xu et al, 2013 ). These markers were designed to be polymorphic among a broad diversity of maize lines (including tropical inbreds), and thus may not be polymorphic among the much more closely related inbreds commonly used for forward genetics.…”
mentioning
confidence: 99%